Exacerbation of branch retinal vein occlusion post SARS-CoV2 vaccination: Case reports. Issue 50 (17th December 2021) - Tanaka, Hayato; Nagasato, Daisuke; Nakakura, Shunsuke; Tanabe, Hirotaka; Nagasawa, Toshihiko; Wakuda, Hiroyuki; Imada, Yoko; Mitamura, Yoshinori; Tabuchi, Hitoshi
Abstract: Rationale: In this paper, we report on 2 patients who developed branch retinal vein occlusion (BRVO) exacerbation 1 day after administration of the BNT162b2 (Pfizer-BioNTech) SARS-CoV-2 vaccine. Patient concerns: Case 1: A 71 year-old female developed vision loss in her left eye 1 day after receiving a second dose of the SARS-CoV-2 mRNA vaccine. This patient was diagnosed with temporal inferior BRVO and secondary macular edema (ME) in her left eye. ME resolved after 3 doses of intravitreal aflibercept (IVA). After treatment, no recurrence of ME was observed. Case 2: A 72 year-old man developed vision loss in his right eye 1 day after receiving the first dose of the SARS-CoV-2 mRNA vaccine. This patient was diagnosed with temporal superior BRVO in the right eye without ME. The patient was followed up and did not undergo any additional treatment. Diagnoses: Case1: Temporal superior BRVO and secondary ME were observed in the left eye. Her best-corrected visual acuity (BCVA) was 20/30. Case2: Temporal superior BRVO recurrence and secondary ME were observed in the right eye. BCVA was 20/25. Interventions: Case1: Additional dose of IVA was administered. Case2: Two times of Intravitreal ranibizumab was administered twice. Outcomes: Case1: Subsequently, ME resolved BCVA was 20/20. Case2: Subsequently, ME resolved BCVA was 20/25. Lessons: Both cases showed a possible association between SARS-CoV-2 vaccination and the exacerbation of BRVO.